Reconstructing the theology of Evagrius Ponticus : beyond heresy - Casiday, Augustine (Cambridge University Press, 2013)
"Evagrius Ponticus is regarded by many scholars as the architect of the eastern heresy Origenism, as his theology corresponded to the debates that erupted in 399 and episodically thereafter, culminating in the Second Council of Constantinople in 553 AD. However some scholars now question this conventional interpretation of Evagrius' place in the Origenist controversies. Augustine Casiday sets out to reconstruct Evagrius' theology in its own terms, freeing interpretation of his work from the reputation for heresy that overwhelmed it, and studying his life, writings and evolving legacy in detail. The first part of this book discusses the transmission of Evagrius' writings, and provides a framework of his life for understanding his writing and theology, whilst part two moves to a synthetic study of major themes that emerge from his writings. This book will be an invaluable addition to scholarship on Christian theology, patristics, heresy and ancient philosophy"--